Temperature Acquisition System for Real Time Application of First Velocity Correction by EDM (Electronic Distance Measurement) - Felipe Andrés Carvajal Rodriguez; Luis Augusto Koenig Veiga; Wilson Alcântara Soares (Geoplanning: Journal of Geomatics and Planning, 2021)
The first velocity correction is used to correct the measured distance affected by the velocity variation of the electromagnetic wave propagation in a medium. This correction depends on the refractive index of the propagation medium and reference refractive index. The influence of the temperature in the medium refractive index is critical; some estimates establish that variation 1°C causes 1ppm of error in distances. In the measuring processes with total stations, the temperature is usually collected at only one point, for example, in the position where the measuring instrument is setup. However, the wave propagates in a medium of non-constant temperature, where the extremes of the line can present variations and thus this measurement in only one point could be non-representative. In this context, it was developed a low-cost real-time temperature acquisition system. This system provides the temperature values in different locations allowing their monitoring through the time. Experiments realized during the geodetic monitoring of a dam, show variations up to 8°C among geodetic points on the dam and around it. An analysis was development to evaluate the influence of temperature variations on monitoring distances and geodetic coordinate of a 2d network with different approaches (temperature modeling).  The results shows different values for distances (1.0 mm) and coordinates (0.5 mm) depending of the approach choose.